New algorithms for smart assessment of math exercises - Araújo, Isabel (2015)
Publicado em "New contributions in information systems and technologies", vol. 1. ISBN 978-3-319-16485-4. Series: Advances in intelligent systems and computing, vol. 353, ISSN 2194-5357